Analisis Pendapatan Usahatani Padi Sawah Di Desa Mongkoinit Kecamatan Lolak Kabupaten Bolaang Mongondow - Damogalad, Ari Sigit; Memah, Melsje Yellie; Pangemanan, Lyndon Reinhard Jacob (AGRI-SOSIOEKONOMI, 2024)
This study aims to calculate and analyze the income of paddy rice farming in Mongkoinit Village, Lolak District, Bolaang Mongondow Regency. The research was carried out for 3 months, from May 2023 to July 2023 starting from preparation to preparation of a research report The data used in this study are primary and secondary data. Primary data were obtained in the research field, namely from interviews with paddy rice farmers, while secondary data were obtained from agencies related to the research.The sample used is purposive sampling (intentionally). Farmers who were sampled were 10 respondents Based on the results of the study, it was shown that the average income of paddy rice farming obtained by farmers in Mongkoinit Village was Rp. 207,500,000 with an average income per hectare of Rp. 20,750,000 The average cost of paddy rice farming costs IDR 115,111,750. With an average cost per farmer of Rp. 11,511,750. Thus, the average rice farming income earned by farmers in 1 planting season in Mongkoinit Village is Rp. 92,388,250 with an average farmer income of Rp. 9,238,825 R/C Ratio, which is 1.80 which is greaterthan 1, indicating that this lowland rice farming is profitable and feasible to cultivate.